2013
DOI: 10.2135/cropsci2012.08.0475
|View full text |Cite
|
Sign up to set email alerts
|

Soil Type and Rooting Depth Affect Hybrid Bermudagrass Injury with Preemergence Herbicides

Abstract: Applications of preemergence (PRE) herbicides can injure hybrid bermudagrass [C. dactylon (L.) Pers. × C. transvaalensis Burtt‐Davy]. Research was conducted to determine the effects of soil texture and rooting depth on hybrid bermudagrass injury with two PRE herbicides. Washed ‘Tifway’ hybrid bermudagrass sod was established in mini‐rhizotrons. Treatments included the factorial combination of two soils (sand, silt loam), four herbicides (indaziflam at 35, 52.5, and 70 g ha−1 and prodiamine at 840 g ha−1), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 20 publications
7
25
2
1
Order By: Relevance
“…Additionally, field experiments evaluating long‐term survival of seedlings established within HPPs are crucial. Soil organic matter content, soil volumetric water content, soil texture, indaziflam application rate, and rooting depth of plants all affect the amount of injury caused by indaziflam to postgerminative establishment of grass species (Gomez de Barreda et al ; Jones et al ; Schneider et al ; Jeffries & Gannon ). The long‐term effects of HPPs have not been studied and it is unknown if they will limit indaziflam injury beyond early seedling growth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, field experiments evaluating long‐term survival of seedlings established within HPPs are crucial. Soil organic matter content, soil volumetric water content, soil texture, indaziflam application rate, and rooting depth of plants all affect the amount of injury caused by indaziflam to postgerminative establishment of grass species (Gomez de Barreda et al ; Jones et al ; Schneider et al ; Jeffries & Gannon ). The long‐term effects of HPPs have not been studied and it is unknown if they will limit indaziflam injury beyond early seedling growth.…”
Section: Discussionmentioning
confidence: 99%
“…Henry et al (25) reported that perennial ryegrass cover in plots treated with indaziflam at 0.053 kg/ha and 0.070 kg/ha measured 37 to 48% compared to 88% for a non‐treated check 257 days after initial treatment. Reduced recovery in response to indaziflam may be explained by research conducted by Jones et al (27). Hybrid bermudagrass injury on sand‐based systems was 25 to 47% 6 WAT in response to indaziflam at 0.035 kg/ha, while reductions in root length density (> 58%) were observed on root systems (5 to 15cm in depth) following applications of indaziflam at 0.035 to 0.070 kg/ha (27).…”
Section: Bermudagrass Recovery In Response To Pre Herbicidesmentioning
confidence: 99%
“…This study indicated that the phytotoxicity effects of indaziflam are greater in soils with low organic carbon content. In a greenhouse study, [ 6 ] indicated that the foliar injury and reductions in root-length density of hybrid bermudagrass from indaziflam were greatest at rooting depth of 5 cm than 10 to 15 cm. Furthermore, the study revealed more indaziflam injuries in hybrid bermudagrass established in sand with no organic carbon than in silt loam with organic carbon.…”
Section: Introductionmentioning
confidence: 99%